Peningkatan Hasil Belajar Siswa Menggunakan Model PBL pada Pembelajaran Tematik Terpadu Kelas IV SD - Hasanah, Tartilatul; Zuryanty, Zuryanty (Universitas Negeri Padang, 2021)
This study aims to describe the improvement of student learning outcomes using the Problem Based Learning model in integrated thematic learning in class IV SDN 01 Campago Ipuh, Bukittinggi City. This type of research is classroom action research using qualitative and quantitative approaches. The subjects of this study were the teacher and 22 fourth grade students. Therefore, the Problem Based Learning model can improve student learning outcomes from integrated thematic learning. The result of observing the learning plan in cycle 1 were 83,33% and the second cycle was 97,22%. Teaher observation in cycle 1 was 82,81 and cycle II was 93,75. While the improvement of aspects of students in cycle I was 82,81 and cycle II was 93,75. While the average student learning outcomes in the aspects of knowledge are 81,25 to 92,09, and in the aspect of skills on average get 83,71 to 93,06